2023
DOI: 10.1021/acs.nanolett.3c01573
|View full text |Cite
|
Sign up to set email alerts
|

Gigantic Anisotropy of Self-Induced Spin-Orbit Torque in Weyl Ferromagnet Co2MnGa

Abstract: Spin-orbit torque (SOT) is receiving tremendous attention from both fundamental and application-oriented aspects. Co2MnGa, a Weyl ferromagnet that is in a class of topological quantum materials, possesses cubic-based high structural symmetry, the L21 crystal ordering, which should be incapable of hosting anisotropic SOT in conventional understanding. Here we show the discovery of a gigantic anisotropy of self-induced SOT in Co2MnGa. The magnitude of the SOT is comparable to that of heavy metal/ferromagnet bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…By integrating the known SOT efficiencies of CoGa (𝑡CoGa = 5 nm, 𝜉DL = 0.042) and Co2MnGa (𝑡Co 2 MnGa = 10 nm, 𝜉DL = −0.052), [54] we have estimated the SOT efficiency of 1.5nm-thick Co2MnGa as −0.006, assuming 𝜆s to be 3 nm. [55] For the 3-nm-thick CoGa layer, the efficiency has been determined to be 0.023. Moreover, theoretical studies have demonstrated that 𝜎𝑧 can be generated in the IMA layer when the direction of the applied current is parallel to its magnetic moment.…”
Section: Layermentioning
confidence: 99%
“…By integrating the known SOT efficiencies of CoGa (𝑡CoGa = 5 nm, 𝜉DL = 0.042) and Co2MnGa (𝑡Co 2 MnGa = 10 nm, 𝜉DL = −0.052), [54] we have estimated the SOT efficiency of 1.5nm-thick Co2MnGa as −0.006, assuming 𝜆s to be 3 nm. [55] For the 3-nm-thick CoGa layer, the efficiency has been determined to be 0.023. Moreover, theoretical studies have demonstrated that 𝜎𝑧 can be generated in the IMA layer when the direction of the applied current is parallel to its magnetic moment.…”
Section: Layermentioning
confidence: 99%